Pelestarian Sejarah Lokal melalui Optimalisasi Fungsi Koleksi Museum : Pengabdian Masyarakat di Museum Sang Nila Utama - Bunari Bunari; Rizki Ananda H; Yusninar Br. S; Muhammad Rafif; Asaroh Delawati; Vini Agustine (Lembaga Pengembangan Kinerja Dosen, 2025)
Museums have an important role in preserving human and natural cultural heritage, with the main task of collecting, maintaining, securing and displaying collections for educational and research purposes. The Sang Nila Utama Museum in Pekanbaru is an example of a museum that focuses on pre serving Riau Malay culture, functioning as a storage place for artifacts as well as a center for learning local history. The use of this museum in the learning process has been proven to increase public understanding, especially students, regarding the socio-cultural life of the Malay community and the history of Riau. With a variety of collections including artifacts, dioramas and miniatures, this museum provides an interactive experience that enriches knowledge of local history, while strengthening a sense of pride in regional and national cultural identity